Quantification of transmission risk in a male patient with a FLNB mosaic mutation causing Larsen syndrome: Implications for genetic counseling in postzygotic mosaicism cases. Issue 10 (6th July 2017) - Bernkopf, Marie; Hunt, David; Koelling, Nils; Morgan, Tim; Collins, Amanda L.; Fairhurst, Joanna; Robertson, Stephen P.; Douglas, Andrew G. L.; Goriely, Anne
Abstract : Risk of transmission to offspring for patients diagnosed with a post‐zygotic (mosaic) mutation can be anywhere between 0–50%, depending on whether the germline is involved. However, in males, it is possible to provide evidence‐based personalized counselling on transmission risk by performing mutation analysis via deep‐sequencing on several tissues, including sperm. Here, we illustrate this approach in the case of a male patient with Larsen syndrome caused by a novel post‐zygotic point mutation in FLNB. Abstract: We report the case of a male patient with Larsen syndrome found to be mosaic for a novel point mutation in FLNB in whom it was possible to provide evidence‐based personalized counseling on transmission risk to future offspring. Using dideoxy sequencing, a low‐level FLNB c.698A>G, encoding p.(Tyr233Cys) mutation was detected in buccal mucosa and fibroblast DNA. Mutation quantification was performed by deep next‐generation sequencing (NGS) of DNA extracted from three somatic tissues (blood, fibroblasts, saliva) and a sperm sample. The mutation was detectable in all tissues tested, at levels ranging from 7% to 10% (mutation present in ∼20% of diploid somatic cells and 7% of haploid sperm), demonstrating the involvement of both somatic and gonadal lineages in this patient. This report illustrates the clinical utility of performing targeted NGS analysis on sperm from males with a mosaic condition in order to provide personalized transmission risk and offer evidence‐based counseling on reproductive safety.